Philippine Quality Award (PQA) Framework as a Way to Thrive During and Beyond the Pandemic: Perspectives from Higher Education Institutions (HEIs) - Primero, Marie (African Journal of Education and Practice, 2025)
Purpose: The COVID-19 pandemic that shocked the world in 2019 intensified the emphasis on the need for organizational quality, agility, and sustainability in all industries worldwide, including the education sector. The pandemic exposed loopholes, areas for improvement, or the lack of organizational development techniques in administrations, including HEIs in the Philippines and in other countries, whereas it also displayed other organizations’ readiness in terms of organizational development and the capacity to change towards greater effectiveness. One prominent and robust framework for sustainability and for thriving during sudden and rapid change, such as the pandemic, is the PQA Framework. PQA Framework users are expected to succeed with their organization-embedded mechanisms for leadership, strategic management, customer focus, knowledge management, human resource focus, and operations focus. This study explored the cases of nine Philippine HEIs using the PQA Framework during the pandemic and studied how they implemented the PQA Framework in a challenging situation using Organizational Development. Methodology: The study utilized qualitative research in the form of a case study. The researcher gathered and analysed the experiences of PQA Implementers, using Thematic Case Analysis based on Braun and Clarke’s techniques. This involved identifying a group of similar cases, reviewing existing literature, and selectively choosing a relevant topic. The group were identified with the criteria that they are using the PQA Framework during the pandemic. Data was transcribed, organized, and coded into themes and patterns, employing both inductive and latent approaches to extract insights. The findings were validated against existing literature to address the research questions and highlight key lessons learned from the respondents' experiences. Findings: PQA Framework was found to have enabled organizations to thrive by facilitating strategic planning, focusing on current needs, and ensuring business continuity and agility among the respondents. In the post-pandemic period, it further supported regular stakeholder feedback, crisis management, technology investment, and a comprehensive view on quality. Unique Contribution to Theory, Practice and Policy: Successful PQA Framework utilization requires careful planning and appropriate metrics, as many organizations struggle due to a lack of understanding of Organizational Development, Change, and Systems Perspective, leading to inefficiencies and failures. The study highlights successful implementers' experiences, offering insights into effective strategies by identifying themes and patterns related to Systems Perspective and Change Concepts that others can refer to.